Type D Personality, Stress Level, Life Satisfaction, and Alcohol Dependence in Older Men - Bejda, Grzegorz; Kułak-Bejda, Agnieszka; Waszkiewicz, Napoleon; Krajewska-Kułak, Elzbieta (Frontiers in Psychiatry, 2021)
Alcohol consumption among older adults is becoming an increasing public health problem due to the rapidly growing elderly population. There is a theory that Type D personality is positively correlated with alcohol dependence. The study aimed to assess the style of coping with stress, emotions and anxiety in elder men addicted to alcohol and the relationship between the above. The study included 170 men aged 60 years and older (mean age - 63 ± 3.1 years) addicted to alcohol staying in the Department of Alcohol Addiction Therapy for Men. They were tested with the questionnaire sheet and the following scales: Perceived Family Wealth (PFW), Family Affluence Scale (FAS), Cantril's Ladder of Life Scale, Satisfaction with Life Scale, Type D Personality Scale-14 (DS14), and the 10-item Perceived Stress Scale (PSS-10). The respondents' wealth on a scale of 1–5 points was assessed on avg. 3.1 ± 0.2. The above was confirmed by the results of the FAS scale study, where the respondents obtained an average of 3.9 ± 1.9 (min. 1, max. 8), which proves their average level of affluence. The evaluation of the satisfaction with life using Cantril's Ladder showed that the respondents were also satisfied with life on average (on average 5.5 ± 1.9). The assessment of life satisfaction using the Satisfaction with Life Scale (SWLS) scale allowed for the conclusion that the respondents were very dissatisfied with their lives (mean 17.2 ± 4.9). The evaluation of the measurement of perceived stress (PSS-10 scale) showed that the respondents obtained an average of 23.5 ± 3.7, and on the sten scale, a mean of 7.7 ± 0.98, which proves a high level of perceived stress. The study using the DS14 scale showed that the respondents were in the negative emotionality (NE) subscale - 17.4 ± 4.5 points, and in the HS scale - 16.2 ± 3.2, which proves that they can be classified as a Type D personality. The participants were very dissatisfied with their lives, with a high perceived stress and Type D personality.